New Localities for Micrarionta Rowelli Mccoiana Willett - Hugh C. Rawls (Hello World!, 1971)
As part of a study supported largely by the Council for Faculty Research, Eastern Illinois University, I conducted a series of explorations into the McCoy, Big Maria and other nearby mountains during the academic year, 1961-1968. The type locality for mccoiana was one of the first sites investigated but no specimens were found and no evidence was turned up to indicate that they might stlll be found in the vicinity of the well.